2003
DOI: 10.1523/jneurosci.23-10-04173.2003
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Associative Long-Term Potentiation by Activation of β-Adrenergic Receptors at CA1 Synapses in Rat Hippocampal Slices

Abstract: The objective of this study was to evaluate the role of ␤-adrenergic receptors in modulating associative long-term potentiation (LTP) induced at CA1 synapses. Two independent Schaffer collateral pathways were stimulated in hippocampal slices. The field EPSP (fEPSP) response evoked in one pathway (the weak pathway) was small, whereas a large response, usually 80 -90% of the maximum, was evoked in the strong pathway. After recording of the baseline fEPSP evoked at 0.033 Hz, LTP of the weak pathway could be assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
100
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 40 publications
8
100
3
Order By: Relevance
“…Since ERK activation is essential for the induction of certain forms of LTP at cortical synapses (Impey et al, 1999;Lin et al, 2003Lin et al, , 2006, we tested whether ERK-dependent LTP could be induced by high-frequency stimulation (HFS) at PBA-CeAC synapses in slices from normal mice and whether LTP induction might share common mechanisms with induction of PKC-ERKdependent potentiation by PDA and with postsynaptic enhancement of PBA-CeAC EPSCs in AIMP animals. As shown in Figure 8 A (squares), after application of three trains of HFS at 100 Hz to slices from normal mice, the PBA-CeAC EPSP was significantly potentiated to 191 Ϯ 30% of baseline (n ϭ 9 cells tested, p Ͻ 0.05, paired t test), and potentiation lasted for at least 30 min.…”
Section: Induction Of Nmdar-pkc-erk-dependent Ltp Of Pba-ceac Epscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ERK activation is essential for the induction of certain forms of LTP at cortical synapses (Impey et al, 1999;Lin et al, 2003Lin et al, , 2006, we tested whether ERK-dependent LTP could be induced by high-frequency stimulation (HFS) at PBA-CeAC synapses in slices from normal mice and whether LTP induction might share common mechanisms with induction of PKC-ERKdependent potentiation by PDA and with postsynaptic enhancement of PBA-CeAC EPSCs in AIMP animals. As shown in Figure 8 A (squares), after application of three trains of HFS at 100 Hz to slices from normal mice, the PBA-CeAC EPSP was significantly potentiated to 191 Ϯ 30% of baseline (n ϭ 9 cells tested, p Ͻ 0.05, paired t test), and potentiation lasted for at least 30 min.…”
Section: Induction Of Nmdar-pkc-erk-dependent Ltp Of Pba-ceac Epscsmentioning
confidence: 99%
“…These plastic changes in synaptic function in the pain-related CNS areas are considered to be a part of the cellular mechanisms underlying the development of central sensitization in chronic pain (Ji et al, 2003). At some cortical synapses, LTP induction requires activation of extracellular signal-regulated kinase (ERK) (Impey et al, 1999;Giovannini et al, 2001;Lin et al, 2003Lin et al, , 2006. Since a biochemical hallmark of chronic pain is increased levels of phosphorylated ERK (pERK) in the DH (Ji et al, 1999;Garry et al, 2005;Wei et al, 2006) (for review, see , it is likely that ERK activity triggered by repeated and excessive noxious stimuli might induce LTP of nociceptive inputs onto DH neurons, thereby resulting in central sensitization.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, several lines of evidence show that the quantitative rule of STDP can vary across synapses in different brain areas, and even on the same dendrites, or axons (3,4). Also, the STDP rule can be dynamically regulated by the activity of adjacent synapses (6) or by the activation of ␤-adrenergic receptors and M1 muscarinic cholinergic receptor (7,8). Therefore, rather than being a stereotypic learning rule, it is clear that STDP is influenced or modulated by various intrinsic and external factors.…”
mentioning
confidence: 99%
“…b-ARs include three subtypes, b1, b2, and b3, which are all present in the nervous system. Extensive behavioral and physiological studies have demonstrated that b-AR activation facilitates long-term potentiation (LTP) (Katsuki et al 1997;Lin et al 2003;Straube et al 2003;Gelinas and Nguyen 2005;O'Dell et al 2010;Connor et al 2011) and enhances memory (Ji et al 2003;Tronel et al 2004;Lemon et al 2009;Miranda et al 2011).…”
mentioning
confidence: 99%